Teams Games Tournament Type Cooperative Learning Model as a Solution to Improve Mathematics Learning Outcomes Integer Calculation Operation Material in Grade VI Students of Al-Azhar Bekasi Elementary School - Cipta, Hendhisca; Budianti, Yudi; Muslimah, Muslimah (AS-SABIQUN, 2023)
Mathematics is one of the most important subjects to be mastered well by students, this is because learning mathematics has benefits for everyday life. This study aims to improve learning outcomes in mathematics in elementary school students and to apply the Teams Games Tournament (TGT) learning model in improving mathematics learning outcomes of elementary school students. This study used a qualitative approach and the data analysis process emphasized the conclusion of comparative literature reviews from several scientific journals. The results showed that using the Teams Games Tournament type cooperative learning model can improve mathematics learning outcomes in the cognitive aspect, thus it can be concluded that the Teams Games Tournament type cooperative learning model can be used as a solution to improve mathematics learning outcomes in elementary schools. Because it is in accordance with the characteristics of elementary school children who like to group, like to play and like to move